2023
DOI: 10.5624/isd.20220133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deep transfer learning with a different kind of lesion on classification performance of pre-trained model: Verification with radiolucent lesions on panoramic radiographs

Abstract: Purpose The aim of this study was to clarify the influence of training with a different kind of lesion on the performance of a target model. Materials and Methods A total of 310 patients (211 men, 99 women; average age, 47.9±16.1 years) were selected and their panoramic images were used in this study. We created a source model using panoramic radiographs including mandibular radiolucent cyst-like lesions (radicular cyst, dentigerous cyst, odontogenic keratocyst, and ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Their original training dataset consisted of 200 samples, with an additional 60 samples in the test dataset. Using a pretrained network, they achieved high recall for Stafne's bone cavity, but only 0.79 for other radiolucent lesions of the mandible [26]. In contrast, in our study, despite having a relatively small dataset, our detection recall reached 0.94.…”
Section: Discussioncontrasting
confidence: 74%
“…Their original training dataset consisted of 200 samples, with an additional 60 samples in the test dataset. Using a pretrained network, they achieved high recall for Stafne's bone cavity, but only 0.79 for other radiolucent lesions of the mandible [26]. In contrast, in our study, despite having a relatively small dataset, our detection recall reached 0.94.…”
Section: Discussioncontrasting
confidence: 74%
“…In recent years, research on diagnostic imaging using deep learning systems has been rapidly progressing, and its usefulness in the maxillofacial region has been reported using panoramic radiographs. 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 A deep learning system is an artificial intelligence machine learning method that allows a computer to learn tasks in the same way as humans, based on a neural network system that imitates the neurons in the human brain. Many authors have reported the clinical usefulness of deep learning systems for panoramic diagnosis, and several studies have addressed the classification of cyst-like lesions including NDCs and radicular cysts.…”
Section: Introductionmentioning
confidence: 99%